2018
DOI: 10.1007/s10461-018-2213-3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Efavirenz During Pregnancy is Associated with Suicidal Ideation in Postpartum Women in Rural South Africa

Abstract: Efavirenz is used for the management of HIV infection during pregnancy in South Africa (SA), but it is contraindicated in patients with history of depression due to possible suicidal ideation. This study compared suicidal ideation 12-months postpartum among women receiving and not receiving efavirenz in rural SA, where high rates of depression have been identified. Antenatal psychological intimate partner violence (IPV; AOR = 1.04), depression (AOR = 1.06) and detection of efavirenz in dried blood spot at 32 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The Efavirenz-containing first-line antiretroviral therapy (ART) has been linked to an increased risk of psychiatric complications. 25 This research also found that higher chances of suicidal thoughts were correlated with the low body mass index of HV/AIDS patients. This may be attributable to the fact that unexplained weight loss is a symptom of advanced disease that affects patients’ physical, mental, and psychological well-being.…”
Section: Discussionmentioning
confidence: 56%
“…The Efavirenz-containing first-line antiretroviral therapy (ART) has been linked to an increased risk of psychiatric complications. 25 This research also found that higher chances of suicidal thoughts were correlated with the low body mass index of HV/AIDS patients. This may be attributable to the fact that unexplained weight loss is a symptom of advanced disease that affects patients’ physical, mental, and psychological well-being.…”
Section: Discussionmentioning
confidence: 56%
“…Another research in South Africa (Mpumalanga) found that during pregnancy, 39% of HIV-positive pregnant women reported suicidal ideation [17]. According to previous research, major depression, partner disclosure status, stigma, age, and partner aggression have been risk factors for suicidal ideation [12,16,[18][19][20][21][22]. A common problem is mental health issues, including suicidal thoughts among HIVpositive perinatal women, which affect the quality of life of the patient and feto-maternal outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…The first longitudinal study sample included 588 women with HIV. 19% of participants reported SI 12-month postpartum when higher levels of physical and psychological IPV were found among these women at that stage ( 65 ). Similar findings were found in the second longitudinal study, which drew its data from a larger RCT longitudinal study.…”
Section: Resultsmentioning
confidence: 99%